2019
DOI: 10.1111/bph.14663
|View full text |Cite
|
Sign up to set email alerts
|

Optostimulation of striatonigral terminals in substantia nigra induces dyskinesia that increases after L‐DOPA in a mouse model of Parkinson's disease

Abstract: Background and Purpose L‐DOPA‐induced dyskinesia (LID) remains a major complication of L‐DOPA therapy in Parkinson's disease. LID is believed to result from inhibition of substantia nigra reticulata (SNr) neurons by GABAergic striatal projection neurons that become supersensitive to dopamine receptor stimulation after severe nigrostriatal degeneration. Here, we asked if stimulation of direct medium spiny neuron (dMSN) GABAergic terminals at the SNr can produce a full dyskinetic state similar to that induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 55 publications
2
25
0
1
Order By: Relevance
“…Previous work showed that this distinct pattern of sensorimotor-dominant gene regulation after L-DOPA treatment is not specific for dynorphin, but extends to other genes as well, for example, the transcription factors dFosB and JunB [ 32 , 73 ], the serotonin receptor 5-HT1B ([ 33 ]; present study), and other genes [ 74 , 75 ]. These findings thus highlight the close association between abnormal signaling in dMSNs of the sensorimotor striatum and dyskinesia, in general [ 76 , 77 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 81%
“…Previous work showed that this distinct pattern of sensorimotor-dominant gene regulation after L-DOPA treatment is not specific for dynorphin, but extends to other genes as well, for example, the transcription factors dFosB and JunB [ 32 , 73 ], the serotonin receptor 5-HT1B ([ 33 ]; present study), and other genes [ 74 , 75 ]. These findings thus highlight the close association between abnormal signaling in dMSNs of the sensorimotor striatum and dyskinesia, in general [ 76 , 77 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 81%
“…These mice were injected with adeno-associated virus (AAV) particles 13-14 weeks before experiments. An AAV vector tagged with enhanced yellow fluorescent protein (eYFP) and expressing channel rhodopsin (ChR2) under the CaMKII promoter (AAV-CaMKIIa-hChR2(H134R)-EYFP, Therapy Center Vector Core, University of North Carolina) was injected into either the left or right vHP under deep surgical anesthesia (1% isoflurane) as described previously (Keifman et al, 2019). Briefly, animals were mounted on a stereotaxic frame (Kopf Instruments), and two 0.5 ml injections of AAV (2.46 Â 10 13 viral particles per ml) at 0.1 ml/min were performed at the following coordinates: 3.3 mm posterior to bregma, 3.3 and 3.2 mm lateral from midline, and 3.2 and 2.7 mm below cortex surface.…”
Section: Slice Physiologymentioning
confidence: 99%
“…Mechanisms underlying l-DOPA induced dyskinesia. Alterations in D1R signalling play a central role in the development of LID, which is causally dependent on D1R activation and signalling [45][46][47][48] . In animal models of PD based on dopamine depletion, D1R signalling becomes more responsive to agonist stimulation, resulting in increased activation of PKA and ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Longterm treatment with l-DOPA in PD patients frequently leads to the emergence of acute l-DOPA-induced dyskinesia (LID), a debilitating adverse drug effect characterized by abnormal involuntary movements 41,42 . In animal models of PD, dyskinesia can also be induced by D1R agonists 43,44 or optogenetic activation of dMSNs [45][46][47] and the development of LID is dependent on D1R activation 48 and signalling through PKA and ERK1/2 49,50 .…”
Section: D1r Agonist Dose-dependently Activates Pka Signalling In Dormentioning
confidence: 99%